Increasing the smoking cessation success rate by enhancing improvement of self-control through sleep-amplified memory consolidation: protocol of a randomized controlled, functional magnetic resonance study - Sarah Gerhardt; Michaela Kroth; Alexandra Seeger; Roland Schmitt; Heiner Fritz; Lorena Diring; Yury Shevchenko; Karen D Ersche; Gordon Feld; Sabine Vollstädt-Klein (BMC Psychology)
Abstract Background Tobacco use disorder (TUD) remains a global health crisis characterized by high relapse rates despite extensive cessation efforts. This study aims to enhance treatment outcomes by addressing the cognitive and neural imbalances associated with habitual and goal-directed behaviours among individuals with TUD. We hypothesise that by integrating high-intensity interval training (HIIT), cognitive remediation treatment (CRT) via app-based chess training and a standard smoking cessation program (SCP) for cognitive control and sleep quality will be improved, thereby facilitating smoking cessation. Methods The study will enrol 140 treatment-seeking smokers aged 18–65 years who meet the DSM-5 criteria for TUD. The participants will be randomly assigned to four groups: CRT + HIIT in the morning, CRT + HIIT in the evening, HIIT alone in the morning, and HIIT alone in the evening. Assessments will be conducted at baseline (T1), postintervention (T2), and at a three-month follow-up (T3) at the Central Institute of Mental Health in Mannheim, Germany. The primary outcomes include abstinence days or amount of alcohol consumed in cases of relapse, as well as craving reduction. Secondary outcomes include improvements in cognitive functions (working memory, response inhibition, and cognitive control), measured through neuropsychological tasks, functional magnetic resonance imaging (fMRI), polysomnography, and self-report questionnaires. The repeated-measures design allows for within-subject comparisons to evaluate intervention effectiveness. Discussion This study aims to provide insights into the mechanisms through which combined CRT and evening HIIT, alongside improvements in sleep quality, can enhance smoking cessation outcomes. The hypothesised benefits on cognitive control and neural activity changes are expected to support better treatment adherence and reduced relapse rates among individuals with TUD. Addressing potential challenges such as high dropout rates through comprehensive participant support is crucial for the study’s success. Findings from this research could inform future therapeutic strategies for TUD, potentially advancing addiction treatment approaches. The integration of novel interventions with established cessation programs underscores the study’s significance in exploring holistic approaches to improving public health outcomes related to tobacco addiction. Trial registration Registered at clinicaltrials.gov/ct2/show/NCT05726045 (Date 04.04.2024).